FACTORS INFLUENCING CONSUMER PURCHASING DECISIONS ON MUSLIM CLOTHING - Joko Mulyono; Helen Parkhurst; Agustini Tanjung; Primaraga Sumantri Indra Wicaksana (SEAN Institute, 2023)
The rapid growth in the Fashion industry, along with the emergence of various brand image brand products circulating throughout Indonesia has caused increasingly fierce competition among producers. This study aims to determine whether product quality, promotion and brand image influence purchasing decisions on consumers in Cikarang Clean Market Zoya, partially or simultaneously. In research using quantitative methods and samples used as many as 96 respondents with incidential sampling technique which is a sampling technique based on chance. T test results From the results of data processing it appears that the value of Sig. for the Product Quality variable is 0.026 <0.05, Sig. for the Promotion variable is 0,000 <0.05, and the Sig. for Brand Image variable is 0.003 <0.05. Thus H0 is rejected. In conclusion: There is a partially significant effect on product quality, promotion and brand image on purchasing decisions. While the results of the F Test test From the results of data processing shows that the probability value that is Sig is equal to 0,000 <0.05. Thus H0 is rejected. In conclusion: There is a significant simultaneous effect between Product Quality, Promotion and Brand Image on Purchasing Decisions. The output data shows the R-Squere score of 0.448, this means that 44.8% of the variation in the purchase decision value is determined by the role of the variation in the product quality, promotion and brand image values. And the rest that is 55.2% variation in the value of the Purchase Decision is determined by the role of the variation in the value of other independent variables.